Penerapan Konseling Analisis Transaksional Dalam Menyikapi Pembelajaran Luring Pasca Pandemi Covid 19 - Saragi, Muhammad Putra Dinata; Khairani, Ulfa; Andini, Andini; Suhartika, Desmy (IAIN Kudus, 2022)
Application of Transactional Analysis Counseling In Responding to Offline Learning After the Covid 19 Pandemic. This study aims to explore and find out and apply transactional analysis counseling in responding to offline learning after the Covid 19 Pandemic. This research is a qualitative research to find out how to apply offline learning to Islamic Counseling Guidance students at UIN North Sumatra. The steps of this research include the stages of observation, interviews and also documentation. From the results of the study, there are several obstacles in the implementation of transactional analysis counseling but can be resolved properly. With transactional analysis counseling students can be more active and creative in expressing opinions in undergoing offline learning after the Covid 19 pandemic. Through transactional analysis counseling students and lecturers can interact directly and some students are even more comfortable and understand the offline learning process with face-to-face interaction. With transactional analysis counseling in offline learning, students' academic value will not only increase but interpersonal relationships will expand because the intimacy that is forged is getting better. Keywords: Transactional Analysis Counseling, Offline Learning, Post Pandemic.